2015
DOI: 10.3109/14756366.2015.1118686
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,5-diphenyl-6-substituted 1H-pyrazolo[3,4-d]pyrimidin-4(5H)-ones induced apoptosis in RKO colon cancer cells

Abstract: Novel 1,5-diphenyl-6-substituted-1H-pyrazolo[3,4-d]pyrimidin-4(5H)-ones were synthesized and characterized. All compounds were screened for their anti-proliferative activities in five different cancer cell lines. The results showed that compounds 7a and 7b comprising aminoguanidino or guanidino moiety at position 6 inhibited proliferation of RKO colon cancer cells with IC 50 of 8 and 4 mM, respectively. Compounds 7a and 7b induced apoptosis in RKO cells, which was confirmed by TUNEL and annexin V-FITC assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…[8,9] In particular, pyrimidine-fused heterocyclic compounds have attracted considerable attention for their promising anticancer activity against a range of cancers, including leukaemia, colon, lung, and breast cancer, through various mechanisms. [10][11][12][13][14][15][16][17][18][19] Within the field of fused heterocyclic compounds, chromenopyrimidines have emerged as a remarkable type of molecules. Numerous studies reported in the literature have identified chromenopyrimidines (I-VII) with a promising profile as potential anticancer agents [20][21][22][23][24][25][26] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9] In particular, pyrimidine-fused heterocyclic compounds have attracted considerable attention for their promising anticancer activity against a range of cancers, including leukaemia, colon, lung, and breast cancer, through various mechanisms. [10][11][12][13][14][15][16][17][18][19] Within the field of fused heterocyclic compounds, chromenopyrimidines have emerged as a remarkable type of molecules. Numerous studies reported in the literature have identified chromenopyrimidines (I-VII) with a promising profile as potential anticancer agents [20][21][22][23][24][25][26] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, pyrimidine derivatives have emerged as a fascinating class of compounds in medicinal chemistry due to their diverse biological and pharmacological properties [8,9] . In particular, pyrimidine‐fused heterocyclic compounds have attracted considerable attention for their promising anticancer activity against a range of cancers, including leukaemia, colon, lung, and breast cancer, through various mechanisms [10–19] …”
Section: Introductionmentioning
confidence: 99%